Edukasi Pencegahan Risiko Tinggi Usia Terlalu Tua (40 Tahun) di Praktek Mandiri Bidan Dewi Ciselia - Ciselia, Dewi; Anggraini, Ririn; Saputra, Andre Utama (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Integrated antenatal care is a comprehensive and quality antenatal service provided to all pregnant women. Complete antenatal examinations are K1, K2, K3 and K4.) This community service is carried out by the Independent Practice of Midwife Dewi Ciselia. Location This implementation will be held in May – June 2024. Participants are 20 people. Methods for conducting counseling using adult learning such as question and answer discussions and video screenings as well as leaflets and posters. material is given and then a posttest is carried out. Before carrying out the counseling there were 18 respondents (90%) who had insufficient knowledge. Can be seen in the table and 2 respondents (02%) with sufficient knowledge, while after carrying out community service Perseta Anusias asked questions after conducting the counseling. The results can be seen in the table above. The results were 20 people (100%). Good knowledge. This means that there is an increase in Perseta's knowledge about Education to Prevent the High Risk of Too Old Age (40 Years) after being given counseling, meaning that the activity provides knowledge.